Commentary: Some help for researching law and religion issues - Calvaruso, Marie (Daily record (Morristown, N.J. : 1971), 2007)
A good resource for international law and religion information is the Brigham Young University International Center for Law and Religious Studies (www.iclrs.org). The Web site contains a dictionary of legal and religious terms, highlights of recent international law and religion news and a collection of papers presented at conferences sponsored by ICLRS. An important feature of the site is the Religion and Law International Document Database -- a searchable collection of global documents relating to law and religion. The database serves as a portal to specific country or regional resources such as laws, regulations and case law. There also is a portal to documents of international organizations such as the United Nations, European Commission of Human Rights and the Inter-American Commission on Human Rights. Journal of Law and Religion (law.hamline.edu/jlr/journal-law-and- religion.html) is an interdisciplinary journal devoted to the study of law, religion and social context published by Hamline University School of Law. It is available by print subscription. The Web site features "Contemporary Conversations" -- the full text of selected articles from recent issues intended to promote timely discussion of current events. Numerous book reviews published in the print journal also are accessible online. The Web site includes tables of contents, current abstracts, and author, title and subject indices. Also included is a list of U.S. Supreme Court decisions relating to religious liberty and church-state relations.